2014
DOI: 10.1093/annonc/mdu266
|View full text |Cite
|
Sign up to set email alerts
|

On demand Gamma-Knife strategy can be safely combined with BRAF inhibitors for the treatment of melanoma brain metastases

Abstract: This series does not show immediate radiotoxicity nor radiation recall, in melanoma patients with BRAF-I whose BMs are treated by GKRS. Interrupting BRAF-I for stereotactic radiosurgery (SRS) of BM seems useless, although it is still advised for other radiation therapies. The potential benefit of combining SRS and BRAF-I can be safely tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 18 publications
0
53
2
2
Order By: Relevance
“…Scalp reactions as well as radiation recall dermatitis have been reported [18,[25][26][27]. However, larger series, such as the study from our group assessing concurrent vemurafenib with SRS, have failed to demonstrate an increased rate of skin toxicity [10,11]. Similarly, in our study with dabrafenib and trametinib administered either before, after, or concurrent with SRS, an increased rate of skin toxicity was not seen with one patient experiencing a grade 1 headache following SRS treatment.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Scalp reactions as well as radiation recall dermatitis have been reported [18,[25][26][27]. However, larger series, such as the study from our group assessing concurrent vemurafenib with SRS, have failed to demonstrate an increased rate of skin toxicity [10,11]. Similarly, in our study with dabrafenib and trametinib administered either before, after, or concurrent with SRS, an increased rate of skin toxicity was not seen with one patient experiencing a grade 1 headache following SRS treatment.…”
Section: Discussioncontrasting
confidence: 45%
“…Recent clinical evidence from our group and others support the safety and efficacy of BRAFi therapy concurrent with radiation therapy in the management of melanoma BMs [10][11][12]. However, to our knowledge, the results of combined BRAF and MEK inhibition with radiation therapy for BRAF mutant melanoma patients with BMs has not been previously reported.…”
Section: Introductionmentioning
confidence: 86%
“…Patel et al reported that BRAF inhibitors increase the rate of RN following SRS [24]. Multiple separate studies have failed to replicate these results, and current consensus guidelines recommend holding BRAF inhibitor therapy for 1 day before and after SRS [4,25].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…However, the radiosensitization effect of BRAF inhibitor also increased the risk of skin toxicities with radiation (133)(134)(135)(136). Due to the minimum skin dose from SRS, several studies that evaluated BRAF inhibitor with SRS for patients with brain metastases reported favorable outcome (137)(138)(139). Studies that directly compared outcomes of patients treated with SRS alone and SRS with BRAF inhibitor suggest that there indeed may be a survival benefit of combination therapy (140)(141)(142).…”
Section: Rt With Concomitant Agentsmentioning
confidence: 99%